MODERN MUSLIMAH IN MEDIA: A STUDY OF RECEPTION ANALYSIS IN “SALIHA” PROGRAM ON NET TV - Eka Perwitasari Fauzi; Feni Fasta; Robert Jeyakumar Nathan; So Won Jeong (ASPIKOM Jabodetabek Region, 2020)
Indonesia, as a country with the largest Muslim population in the world, holds a significant market share of the Islamic industry, especially for Muslim women. This study discusses how media constructs meaning for modern Muslim women's identity, in